301 ways to have fun at work - Hemsath, Dave, 1961- (BK business book., 1997)
"The most successful organizations add a healthy dose of play into their daily or weekly routines. In fact, research has shown that when people actually enjoy their jobs they're more creative, more productive, and more committed to doing their jobs well. Companies like the Colorado Health Sciences Center and Southwest Airlines attest to the positive effect of fun at work. Both trace increased job satisfaction and decreased employee downtime to concerted efforts to make fun a part of their corporate identity"--EBL